Descartes' Proof for the Existence of God: Premises and Intentions - Jankauskas, Skirmantas (Problemos, 2004)
The article deals with Descartes’ Meditations, where his proof for the existence of God is taken as the starting point of the analysis. An attempt is being made to prove that namely this Proof of the Existence of God serves as the axis for the Meditations of Descartes, though the subsequent philosophy attributed a considerably greater significance to the cogito principle. At the same time, there is also supported the traditional attitude that the most important discovery of Descartes is precisely the cogito principle, which initiates the modern thinking. The principle is being discussed by separating the contexts of its discovery and justification. It is maintained that this principle is directly implied by the structure of constructive thinking in natural science, while the hyperbolic doubting is just a tool used by Descartes to expose the principle. However, the new principle needs legalization, and the proof of God is the means by which Descartes adjusts the new principle to the traditional thinking. The connection with God established by the proof implies a possibility to assimilate the content of traditional thinking by means of the new principle, with it subsequently being shaped in accordance with the requirements of the cogito. Therefore, the article reveals the friction between the new principle and the traditional thinking, and highlights the changes in the structure of traditional thinking that are caused by the friction and determine the ramifications of the subsequent philosophical trends. The article is concluded with the idea that the proof of God fails to fortify belief, contrary to the assumption of Descartes, but rather paves the way for the deconstruction of belief and the traditional thinking which is based on this belief.
Keywords: modern philosophy; proof of god; cogito; knowledge; traditional thinking; deconstruction